The Relationship Between Student Motivation And Discipline In Participating Scouting Extracurricularies At SMP Labschool UNP - Titik Mai Indra; Solfema Solfema (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
Based on observations and conversations with students who took part in scouting extracurriculars, in this study there were students who lacked enthusiasm and seriousness in participating in these activities. This is thought to be caused by a lack of student motivation in taking part in scouting extracurricular activities at SMP Labschool UNP. So there are concerns that it could affect students' discipline in participating in scout extracurriculars. The purpose of this research is to see a picture of student motivation in taking part in scout extracurriculars, see a picture of student discipline in taking part in scout extracurriculars, as well as the relationship between motivation and student discipline in taking part in scout extracurriculars at SMP Labschool UNP. This research uses correlational methodology as a form of quantitative research. The population is 150 people consisting of classes VII and VIII who are registered as scout members at SMP Labschool UNP. Using a stratified random sampling approach, the research sample consisted of 45 respondents or 30% of the population. Questionnaires were used as a data collection method. Meanwhile, for data analysis, descriptive analysis was used using the percentage formula, and correlational analysis was used using the product moment formula.Based on research conducted at SMP Labschool UNP, it shows that student motivation in taking part in scout extracurriculars is categorized as low, student discipline in taking part in scout extracurriculars is also categorized as low, and there is a significant relationship between motivation and student discipline in taking part in scout extracurriculars at SMP Labschool UNP. It is hoped that the suggestions from the researchers will enable supervisors and school administrators to create a more attractive physical and social environment, create new ideas or ways that are creative and fun so that they can attract the maximum attention of pupils and students so that students are diligent and diligent and enthusiastic about participating in activities. .Keywords: motivation, discipline, scout extracurricular, Nonformal